Kidney developmental effects of metal-herbicide mixtures: Implications for chronic kidney disease of unknown etiology. (November 2020) - Babich, Remy; Ulrich, Jake C.; Ekanayake, E.M. Dilini V.; Massarsky, Andrey; De Silva, P. Mangala C.S.; Manage, Pathmalal M.; Jackson, Brian P.; Ferguson, P. Lee; Di Giulio, Richard T.; Drummond, Iain A.; Jayasundara, Nishad
Highlights: Chemical mixtures are found in drinking water in CKDu impacted farming communities. Drinking water derived from CKDu endemic regions affect mitochondrial function. Mixtures of As, Cd, V, and Pb, even at safe levels, can perturb kidney development. Abstract: Chronic kidney disease of unknown etiology (CKDu) is an emerging global concern affecting several agricultural communities in the Americas and South Asia. Environmental contaminants such as heavy metals (e.g., Cd, As, Pb, and V) and organic pesticides (e.g., glyphosate) in the drinking water have been hypothesized to play a role in childhood onset and progression of this disease. However, a comprehensive analysis of chemical contaminants in the drinking water and effects of these compounds and their mixtures on kidney development and function remains unknown. Here, we conducted targeted and non-targeted chemical analyses of sediment and drinking water in CKDu affected regions in Sri Lanka, one of the most affected countries. Using zebrafish Danio rerio, a toxicology and kidney disease model, we then examined kidney developmental effects of exposure to (i) environmentally derived samples from CKDu endemic and non-endemic regions and (ii) Cd, As, V, Pb, and glyphosate as individual compounds and in mixtures. We found that drinking water is contaminated with various organic chemicals including nephrotoxic compounds as well as heavy metals, but at levels considered safe for drinking. Histological studies and gene expression analyses examining markers of kidney development ( pax2a) and kidney injury ( kim1) showed novel metal and glyphosate-metal mixture specific effects on kidney development. Mitochondrial dysfunction is directly linked to kidney failure, and examination of mixture specific mitochondrial toxicity showed altered mitochondrial function following treatment with environmental samples from endemic regions. Collectively, we show that metals in drinking water, even at safe levels, can impede kidney development at an early age, potentiating increased susceptibility to other agrochemicals such as glyphosate. Drinking water contaminant effects on mitochondria can further contribute to progression of kidney dysfunction and our mitochondrial assay may help identify regions at risk of CKDu.